Direct displacement-based design of coupled walls with steel shear link coupling beams. (December 2021) - Malla, Niraj; Wijeyewickrema, Anil C.
Highlights: Direct displacement-based design (DDBD) for coupled walls with shear link coupling beams using inelastic displacement spectra. Capacity design: Continuum model of coupled walls is used for shear force and bending moment estimation. Drift of the coupled walls is restricted within desired limits. Predicted shear force demands show good accuracy and bending moment demands show moderately good results. Abstract: Coupled walls with replaceable steel shear link coupling beams are used to minimize the repair cost and downtime of buildings after major earthquakes. In this study, the direct displacement-based design (DDBD) method for coupled walls with steel shear link coupling beams using inelastic displacement spectra is developed. For capacity design, a continuum model of the coupled walls that accounts for the stiffness degradation due to expected damage in the first mode is adopted, to obtain equations to estimate the shear forces and bending moments generated due to higher modes. The effectiveness of the DDBD design method for coupled walls with steel shear link coupling beams is assessed by comparing the drift demands with nonlinear response history analysis (NLRHA) results and for capacity design purposes the shear force and bending moment profiles obtained from NLRHA are compared with the results obtained from the equations derived in this study and the weighted capacity design (WCD) method. The results obtained for 5-, 10-, and 15-story coupled walls with steel shear link coupling beams, show that the proposed design methodology is suitable to achieve the design objectives.